EKSPRESI SENI RITUAL MASYARAKAT TUTUP NGISOR - Ansari, Isa (Institut Seni Indoensia Surakarta, 2016)
This paper is presented to the reader is presented to describe the ritual art forms and restrictions made by local people to the art they present. Due to these restrictions they realize the implications of their art performing. To explain these realities the author uses anthropological perspective about the experience, which emphasizes the bodily and mental disposition of the local community.Methodological implications that emerges is that the interviews and observations intent should be done to the informant. From the analysis, that the ritual arts community in Tutup Ngisor village done to support the sustainability of the arts in the area.Keywords: Expression, Ritual Art, Tutup Ngisor.